American Civil Liberties Union of Northern California Honors Howard Watkins with Lola Hanzel Courageous Advocacy Award - Watkins, Howard::::::::: (1987)
Hon. Cruz Reynoso, Drucilla Ramey, Howard Watkins and Lee Halterman seated at headtable Luncheon at Sheraton Palace Hotel in San Francisco